Bone metabolism disorders in endogenous Cushing syndrome - Cylke -Falkowska, Karolina; Stelmachowska-Banaś, Maria (Wiedza Medyczna, 2023)
Endogenous Cushing syndrome (CS) leading to an overproduction of cortisol is a major cause of secondary osteoporosis. Bone complications in CS, despite the fact that they not only reduce the quality of life, but also increase mortality, are still underdiagnosed. Hypercortisolemia results, among others, in a reduced bone mineral density (BMD). However, an increased risk of fracture in CS may occur in bones with only a slight reduction or even normal BMD. The disease is usually insidious, prolonging the period of hypercortisolemia before diagnosis. Therefore, skeletal complications such as reduced BMD, osteoporosis and fractures are common in CS. Osteoporosis has a prevalence of 40-70%, osteopenia 80-85% and fractures 30-70% in patients with CS (1, 2). Fractures usually involve the lumbar and thoracic vertebrae, hips, ribs and pelvis as the trabecular bone is mainly affected. The most common pathogenesis of CS leading to bone lesions remains a topic of researches. Chronic hypercortisolemia leads not only to the reduction of BMD but also to changes in bone microarchitecture. Increased resorption and inhibited bone formation are the main mechanisms described in CS. Reversal of changes in bone mineral density after recovery from CS has been observed. Surgical treatment of pituitary or adrenal tumours should be the first line of treatment. However, vitamin D and calcium supplementation as well as treatment with antiresorptive drugs seems to be also essential. In this paper we presents a review of the current literature on bone complications in endogenous CS.